2005
DOI: 10.1196/annals.1338.030
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Inflammatory and Antioxidative Effects of Propofol on Lipopolysaccharide‐Activated Macrophages

Abstract: Sepsis is a serious and life-threatening syndrome that often occurs in intensive care unit (ICU) patients. During sepsis, inflammatory cytokines and nitric oxide (NO) can be overproduced, causing tissue and cell injury. Propofol is an intravenous agent used for sedation of ICU patients. Our previous study showed that propofol has immunosuppressive effects on macrophage functions. This study was designed to evaluate the anti-inflammatory and antioxidative effects of propofol on the biosyntheses of tumor necrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 23 publications
4
97
0
Order By: Relevance
“…Propofol has been proposed to decrease lipid peroxidation and activate the immune system (13). Conversely, propofol has also been reported to inhibit immune cell functions, such as LPS-induced cytokine release and the oxidative stress response (10). Propofol also attenuates Kupffer cell activation and LPS-induced hepatocellular damage (57,58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Propofol has been proposed to decrease lipid peroxidation and activate the immune system (13). Conversely, propofol has also been reported to inhibit immune cell functions, such as LPS-induced cytokine release and the oxidative stress response (10). Propofol also attenuates Kupffer cell activation and LPS-induced hepatocellular damage (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Propofol is also known to alter the functions of immunocompetent cells, such as neutrophils, monocytes, and macrophages (10,11,36). Propofol decreases proinflammatory cytokine production and inducible nitric oxide synthase expression in LPS-stimulated mouse macrophage Raw 264.7 cells (10,11) and increases bacterial accumulation in lung and liver after venous infusion compared with the effects of saline infusion (26). Propofol binds to the ␤ 2 -subunit of the GABA A receptor (4,16), which regulates Cl Ϫ channels (32).…”
mentioning
confidence: 99%
“…Previous studies indicated that the well-known anti-oxidant properties of propofol might be related to its chemical structure, which is similar to that of phenol-based scavengers such as tocopherols. 1,9,[42][43][44] Indeed, a-tocopherol is reported to have a strong anti-oxidizing effect. 42 Similarly, propofol's inhibitory effect on COX might be ascribable to its structural similarity to c-tocopherol.…”
Section: Lps Pretreatmentmentioning
confidence: 99%
“…Propofol has been proven to inhibit pro-inflammatory cytokines induced by lipopolysaccharide, including IL-b, IL-6 and TNF-a. These cytokines play important roles in pain signalling [3]. Propofol scavenges free radicals with a fast and stable kinetic feature in vitro, which is useful and important for understanding its anti-oxidant properties, and may also play a role in dynamic protection in the body [4].…”
Section: Introductionmentioning
confidence: 99%